Genre features of the press release (Herald of Journalism, 2018)
The article deals with genre features press releases prepared by the press-service. The main factors influencing the selection and organization of materials for the press-service, the author considers the redundancy information and genre isolation text. The first sign is realized in the text of the release through a variety of repetitions, allowing an association to improve the company’s name and the scope of its activities. The second sign is expressed in the same type used phrases.Key words: Press release, bekgraunder, news release, information, genre.